The current state of the Steppe Eagle Population in the Republic of Kalmykia, Russia - Anton A. Abushin; Gennady I. Erdnenov (Пернатые хищники и их охрана)
In the middle of the XX century, the Steppe Eagle (Aquila nipalensis) was almost ubiquitous and abundant in southern Russia. However, due to the total plowing of the steppe, the decline of traditional pasture cattle breeding, the construction of power line infrastructure and other negative factors, the numbers of this species declined everywhere by the end of the XX century. Currently, the Steppe Eagle has practically stopped breeding in Rostov Region and Stavropol Krai, remaining only in the areas bordering Kalmykia in the number of several dozens of pairs. The modern boundary of the continuous breeding range of the Steppe Eagle in Europe is settled on the territory of Kalmykia (789 pairs on average) and the Volgograd Zavolzhye (300– 500 pairs) in the west, going further east to Kazakhstan and to the regions of Russia transboundary with this country.